Default Mode Network Abnormalities in Bipolar Disorder and Schizophrenia - Öngür, Dost (2010)
The default-mode network (DMN) consists of a set of brain areas preferentially activated during internally focused tasks. We used functional MRI to study the DMN in bipolar mania and acute schizophrenia. 17 bipolar disorder (BD), 14 schizophrenia (SZ) and 15 normal control (NC) subjects underwent 10-minute resting scans. The DMN was extracted using independent component analysis and template-matching; spatial extent and timecourse were examined. Both patient groups showed reduced DMN connectivity in the medial prefrontal cortex (mPFC) (BD:x=-2,y=54,z=-12; SZ:x=-2,y=22,z=18). BD subjects showed abnormal recruitment of parietal cortex (correlated with mania severity) while SZ subjects showed greater recruitment of the frontopolar cortex/basal ganglia. Both groups had significantly higher frequency fluctuations than controls (frequency × diagnosis:F(43,2)=3.183,p=0.05). We found ventral mPFC abnormalities in BD and dorsal mPFC abnormalities in SZ. The higher frequency of BOLD signal oscillations observed in patients suggests abnormal functional organization of circuits in both disorders. Further studies are needed to determine how these abnormalities are related to specific symptoms of each condition.